2023
DOI: 10.1021/jacs.3c08079
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electroreduction of Carbonate to Formate

Haibin Ma,
Enric Ibáñez-Alé,
Ramesha Ganganahalli
et al.

Abstract: A cause of losses in energy and carbon conversion efficiencies during the electrochemical CO 2 reduction reaction (eCO 2 RR) can be attributed to the formation of carbonates (CO 3 2− ), which is generally considered to be an electrochemically inert species. Herein, using in situ Raman spectroscopy, liquid chromatography, 1 H nuclear magnetic resonance spectroscopy, 13 C and deuterium isotope labeling, and density functional theory simulations, we show that carbonate intermediates are adsorbed on a copper elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Moreover, the theoretical research on Fe-Porphyrin also indicated that the direct electrochemical conversion of CO 3 2− /HCO 3 − is feasible. Actually, there have been reports indicating that both carbonate 45 and bicarbonate 46 could be directly electrochemically reduced into formate. Compared to CO 3 2− /HCO 3 − electrolyzers that rely on the in situ generation of CO 2 , direct CO 3 2− /HCO 3 − electrolysis technology makes it easier to achieve full utilization of carbon.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the theoretical research on Fe-Porphyrin also indicated that the direct electrochemical conversion of CO 3 2− /HCO 3 − is feasible. Actually, there have been reports indicating that both carbonate 45 and bicarbonate 46 could be directly electrochemically reduced into formate. Compared to CO 3 2− /HCO 3 − electrolyzers that rely on the in situ generation of CO 2 , direct CO 3 2− /HCO 3 − electrolysis technology makes it easier to achieve full utilization of carbon.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Further, recently, Ma et al reported a direct carbonate electroreduction to formate. [15] Based on these considerations, Cu 2 (OH) 2 CO 3 , containing carbonate groups and Cu that is widely used in C 2 production, was chosen as the candidate to investigate whether the lattice carbonate could be involved in the CO 2 RR to C 2 products. Combined 13 C stable isotope ratio mass spectrometry (IRMS) tests with experiments, we proved that lattice carbonate could act as a mediator to connect external CO 2 molecules to active Cu atoms on Cu 2 (OH) 2 CO 3 surface, which is named lattice carbonate mediated mechanism (LCMM).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the first works in the electrochemical upgrading of CO 2 from amine and bicarbonate capture solutions by us and others have shown that it is the small amounts of dissolved and free CO 2 in equilibrium with the capture solutions that are being reduced electrochemically to carbon monoxide on silver electrodes. [7][8][9][10] Higher temperatures increase the partial pressure of dissolved CO 2 in equilibrium with the capture solution and lead to higher partial current densities for CO 2 reduction products at the expense of a higher thermal energy requirement. 7,11 So far, mainly silver catalysts have been studied systematically for the electrochemical upgrading of amine and bicarbonate capture solutions, and only recently copper has been shown to be able to upgrade carbonates with Faradaic efficiencies of 0.61% under pulse electrolysis conditions.…”
Section: Introductionmentioning
confidence: 99%
“…7,11 So far, mainly silver catalysts have been studied systematically for the electrochemical upgrading of amine and bicarbonate capture solutions, and only recently copper has been shown to be able to upgrade carbonates with Faradaic efficiencies of 0.61% under pulse electrolysis conditions. 9 In the RCC works reported so far, hydrogen evolution reaction (HER) dominates, and it is already evident that interactions of the capture agent with the catalyst increase the complexity of these systems compared to those where only CO 2 and the catalyst are considered.…”
Section: Introductionmentioning
confidence: 99%